Monitoring the effect of hypoxia in bowel dialysate metabolites levels with online biosensors - Córcoles, E. P.; Boutelle, M. G.; Deeba, S.; Hanna, G. B.; Darzi, A. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/